Fibra de crital fotônico: fundamentação e aplicações - Oliveira, Kenny Michele Barreto de (2002)
The main purpose of this dissertation, consists of the study and analysis of the PBG (Photonic Band Gap )..tecnology incorporated in optical fiber structures. So, we'l1 present a complete PBG structure theory, and folowing this, we'l1 present also a chapter for convencional optical fiber, due to the need to construct the base theory of them, and latter a more complete work about photonic crystal fiber. Finaly, we'l1 show the results of the signals , dispersion, and obtained curves under the right dimensions according to the required signals, for convencional optical and photonic crystal fiber. Knowing that PBG crystals with low losses act as perfect mirrors for forbidden frequences and knowing that the persence of structures of PBG as substrates, brings some desirable characteristics such as spontaneous emition supression and superficial waves. We' 11 show according to these characteristics its applications in telecomunication. Therefore, the enphasis of this work is to show that the optical fibers are the only practible thing to integrate the enormous quantity of data and video at intemet' s market, developing, manipulating, changing, and multiplexing the optical fibers chanels in an area where we expect that the photonic crystals has an important hole, since the photonic crystals can be projected and made to avoid losses in the bands of certain wavelength which permits the increase in efficiency ofthe optical components projected with crystals. A sequence of this work would be the utilisation of the PBG structures in the new system of optical network without fiber developed by Bell laboratories of the lucent tecnology, last year using light rays for transmiting information through the air. The new system of optical networks without fiber will permit sending the data of 15 cd-rooms in less then one second, what represents 65 times more information than those transmitted through the actual radio frequences